Applications of Gas Separation by Adsorption for the Future - S. Sircar (Adsorption Science & Technology)
The separation and purification of gas mixtures by adsorption has found numerous industrial applications during the past 30 years. The very active research and development in this field is driven by (a) the highly flexible nature of cyclic adsorptive process designs, (b) the availability of many adsorbents for the separation and (c) the multiple choice of adsorbent–process design combinations for achieving the desired separation goals. The trend is to improve the product quality and separation efficiency, as well as to increase the scale of application of this technology. The design of processes using faster cycles and the use of innovative adsorber configurations are two new directions. Hybrid gas separation and production concepts such as adsorbent membranes and simultaneous sorption–reaction schemes are emerging areas that may open new frontiers of application for this technology.